2021
DOI: 10.1084/jem.20210198
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike therapeutic antibodies in the age of variants

Abstract: Christos Kyratsous, Vice President of Research, Infectious Diseases, and Viral Vector Technologies at Regeneron Pharmaceuticals, and Alina Baum, Associate Director, Infectious Diseases Associate at Regeneron Pharmaceuticals, discuss the development of antibody therapeutics targeting the spike protein of SARS-CoV-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…A cocktail of bamlanivimab and etesevimab is reported to perform better than monotherapy against this variant [ 64 ]. Contrary to this, a combination of casirivimab and imdevimab or COV-2130 and COV2196 have shown no loss in neutralization potency against all VOCs including B.1.427 and B.1.429 [ 65 ]…”
Section: Currently Circulating Variants Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…A cocktail of bamlanivimab and etesevimab is reported to perform better than monotherapy against this variant [ 64 ]. Contrary to this, a combination of casirivimab and imdevimab or COV-2130 and COV2196 have shown no loss in neutralization potency against all VOCs including B.1.427 and B.1.429 [ 65 ]…”
Section: Currently Circulating Variants Of Sars-cov-2mentioning
confidence: 99%
“…A cocktail of bamlanivimab and etesevimab is reported to perform better than monotherapy against this variant [64]. Contrary to this, a combination of casirivimab and imdevimab or COV-2130 and COV2196 have shown no loss in neutralization potency against all VOCs including B.1.427 and B.1.429 [65] One broad-spectrum coronavirus antibody, VIR-7831 is effective against these widely circulating VOCs [64]. Neutralization action of casirivimab/imdevimab cocktail and VIR-7831 mAb which was recently reported to provide 85% protection against COVID-19 related hospitalization and deaths, was unaffected by L452R mutation [63].…”
Section: B1427 and B1429mentioning
confidence: 99%
“…The beta variant of SARS-CoV-2 also carries this mutation, which stabilizes the spike protein trimers and thus provides a transmission advantage [ 7 ]. In addition, the N501Y mutation in the spike protein of the SARS-CoV-2 beta variant has been associated with increased viral infectivity and transmission by enhancing the binding affinity of the spike protein to the human ACE2 receptor [ 41 , 42 ]. This increased affinity may explain the higher viral loads observed in individuals infected with the beta variant, as well as its greater transmissibility and vaccine efficacy compared to earlier strains of SARS-CoV-2 [ 43 ], highlighting the importance of continued surveillance and research on the evolution and spread of the SARS-CoV-2 virus.…”
Section: Discussionmentioning
confidence: 99%
“…Although hundreds of potent nAbs have been successfully isolated (cf., [ 290 , 321 ]), studies on antibody resistance have demonstrated that rapid viral escape arises with any monotherapy regardless of antibody neutralizing activity and epitope conservation [ 322 324 ]. Thus, many researchers and companies have turned to a rational combination of at least two neutralizing antibodies that possess different, non-overlapping epitopes together as a combination therapeutic to provide broader epitope coverage, and hopefully, greater resistance against variants that may arise over time [ 211 , 245 , 261 , 325 ].…”
Section: Anti-sars-cov-2 Igg Antibodiesmentioning
confidence: 99%